2002
DOI: 10.1523/jneurosci.22-08-03090.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Role for α-Synuclein in the Regulation of Dopamine Biosynthesis

Abstract: The alpha-synuclein gene is implicated in the pathogenesis of Parkinson's disease. Although alpha-synuclein function is uncertain, the protein has homology to the chaperone molecule 14-3-3. In addition, alpha-synuclein can bind to 14-3-3, and both alpha-synuclein and 14-3-3 bind to many of the same proteins. Because 14-3-3 binds to and activates tyrosine hydroxylase, the rate-limiting enzyme in dopamine (DA) biosynthesis, we explored whether alpha-synuclein also bound to tyrosine hydroxylase and influenced its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
529
3
22

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 607 publications
(577 citation statements)
references
References 70 publications
(84 reference statements)
23
529
3
22
Order By: Relevance
“…Recent data suggest that ␣-synuclein regulates dopamine synthesis by interacting with tyrosine hydroxylase, inhibiting its activity and leading to a reduction in dopamine synthesis (8). Overexpression of human ␣-synuclein has been shown to cause death of dopaminergic neurons in human primary cultures (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data suggest that ␣-synuclein regulates dopamine synthesis by interacting with tyrosine hydroxylase, inhibiting its activity and leading to a reduction in dopamine synthesis (8). Overexpression of human ␣-synuclein has been shown to cause death of dopaminergic neurons in human primary cultures (19).…”
Section: Discussionmentioning
confidence: 99%
“…TOGA identified differential expression of both known genes and 3Ј ESTs. Of the genes that were differentially expressed in the iP and iNP, ␣-synuclein was prioritized for further investigation because it was located in a region of mouse chromosome 6 syntenic to the rat chromosome 4 QTL, and it was shown to modulate dopamine transmission (8), which is likely involved with neurodegenerative and neuropsychiatric disorders such as alcoholism.…”
mentioning
confidence: 99%
“…Clones expressing dopamine were designated as MN9D and those with no dopamine were designated as MN9X. These cell lines have been extensively characterized previously (17,18,21).…”
Section: Methodsmentioning
confidence: 99%
“…One theory suggested that -synuclein might be linked to PD via the regulation of dopamine (DA) homeostasis [19][20][21][22][23] . Several studies have proposed that -synuclein may be involved in regulating the biosynthesis, vesicles storage and release, as well as reuptake of DA [24][25][26][27][28][29][30][31] . In addition, -synuclein, as a chaperone, has been reported to interact with many other proteins, including 14-3-3, ERK1/2, parkin, etc.…”
Section: Introductionmentioning
confidence: 99%